Situation complexity: delineating situational factors affecting individual communicative action in problem solving - Arina Anis Azlan,; Samsudin A Rahim, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The rapid development of new social media technologies has provided today’s individual with a variety of communicative tools that enable the dissemination of information to large groups of people in a very short amount of time. Individuals who converge into collectives are viewed as influential forces in the creation of problem perception, and have the potential to influence society and pressure the organisations within it. For this reason, understanding audiences and managing information is of interest to communications practitioners and scholars alike. Of late, the study of the individual problem solving process has become an important focus; more specifically, the communicative behaviour of individuals and the factors that influence these communicative behaviours. Previous studies have examined three key antecedent factors that determine an individual’s participation in communicative action: problem recognition, involvement recognition, and constraint recognition. This study proposes that the problem solving process is also influenced by contextual factors that may limit or encourage communicative behaviour. The purpose of this study was to delineate the “situation” in the individual problem solving process and construct a quantitative measure of perceived situation complexity. A synthesis of extant literature produced preliminary dimensions and items that were tested through a survey distributed among 152 university students. Exploratory factor analysis yielded six main dimensions: solution complexity, referent criterion, negative feelings toward the problem, environmental salience, problem familiarity, and uncertainty of a solution. These results provide initial guidance into exploring the concept of context in individual problem solving and the consequences on communicative action.